(untitled) (Marketing Journal, 2025)
This article provides an in -depth analysis of the factors influencing the formation of a regional image, the structural elements of the territorial marketing complex, and the theoretical foundations of the concepts of “image” and “brand.” The study substan tiates the role and significance of marketing strategy in creating a regional image. It also highlights the effective use of communication policy, branding, public relations (PR), and digital marketing tools in shaping a positive image of the region. The a rticle develops recommendations for strengthening the regional image and integrating it with investment attraction, tourism, and socio -economic development. The findings show that the systematic application of marketing strategies enhances regional competi tiveness, builds a reliable image among external audiences, and strengthens brand identification.